Industrial Characteristics and Scientific Collaborations of Taiwanese Companies with High Scientific Productivity - Yu-Wei Chang (Journal of Library and Information Studies, 2016)
This paper identified productive companies in Taiwan, analyzed the industrial categories of productive companies, and investigated the types of institutions collaborating with productive companies, based on articles published between 1982 and 2011. Results indicated that majority of top 50 productive Taiwanese companies belong to electronic industries. The percentage of top 50 productive companies related to electronics has increased during three ten-year periods in a row. Approximately 92% of top 50 productive companies are high-tech industries. However, partial low-tech companies were listed in the top 8 productive companies. A stable trend was observed in the annual percentage of articles coauthored by researchers from the productive companies and domestic universities. Researchers in different companies also coauthored articles, indicating industries do not always compete with each other. (Article content in Chinese with English extended abstract)